Inovasi Pembelajaran: Pengembangan Media Interaktif Sistem Pencernaan untuk Meningkatkan Prestasi Belajar pada Siswa Madrasah Ibtidaiyah - Wijayanto, Adi; Khoiriyah, Sheni Umi; Setyowati, Eni; Taman, Mona Refaat (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2023)
This research is motivated by the presentation of media in print which is still considered less interesting, because it tends to be boring in learning. For this reason, new breakthroughs are needed in presenting material with interesting summaries. This research and development uses research and development (R&D) research methods using the ADDIE model. As a result of this research and development, the researcher concluded that interactive learning media based on Adobe Animation can improve science learning outcomes for class V at MI Modern Mutiara Iman Ngunut Tulungagung. The research results showed that interactive media was declared feasible by experts with an average score of 92%. The use of interactive media received a positive response from teachers, getting 84% and a positive response from students getting 91%. The media was effectively used by students with the results of an increase in the average pre-test and post-test scores of 88%. Thus, interactive media based on Adobe Animation is declared feasible, practical and effective for use as interactive learning media in class V science studies learning in elementary schools.